Effect of quince seed gum (QSG) on the performance of injectable hyaluronic acid hydrogels in terms of the rheological, morphological, and mechanical aspect - KAYAMAN APOHAN, NİLHAN (My University, 2024)
Injectable hydrogels play an important role in tissue engineering as a filling and repairing material. This study aimed to develop a new injectable hydrogel based on hyaluronic acid (HA) and quince seed gum (QSG) and investigate the effect of QSG on hydrogel performance. The amount of unreacted 1,4-Butanediol diglycidyl ether is maintained at an undetectable level for HA-QSG hydrogels. Amino acid analysis showed that the HA-QSG hydrogel had rich amino acid concentrations of leucine, arginine, and valine. After thermal sterilization, the elastic modulus of HA-QSG gels for dermal and intraarticular filler applications is 63 Pa and 92 Pa, respectively. Pore size was found below 200 µm and the dense homogeneous pore structure was observed. Key words: Hydrogel, quince seed gum, rheology, dermal filler injection, intraarticular injection
Keywords: Kimya; Temel Bilimler; Chemistry; Natural Sciences; Temel Bilimler (SCI); Natural Sciences (SCI); CHEMISTRY; Genel Kimya; Fizik Bilimleri; General Chemistry; Physical Sciences; dermal filler injection; Hydrogel; intraarticular injection; quince seed gum; rheology